The harmonization of animal protection during transport in the European Union - Analysis of the sanctioning systems in Italy, Romania and Spain - Silvia Meriggi (Universitat Autonoma de Barcelona. Facultat de Dret, 2020)
In the last sixty years, countries in Europe developed a common legal framework for the protection of so-called “farmed” Animals: on farms, during transport and at the time of their killing. This document describes the most relevant aspects of the sanctioning systems implementing the legislation on the protection of Animals during transport in three countries: Italy, Spain and Romania. These nations were chosen in connection with the author’s collaboration with the German non-governmental organization, Animals´ Angels. The association has been investigating animal transports at the international level since 1998, with particular attention to these three countries. The article draws on findings collected from the organization’s field experience as well as perspectives that have emerged over time during the analysis of the various countries. This document aims to lay out the positive and the negative points of each penalty system, as a basis for a wider analysis, and to formulate proposals for a better and uniform application of a dissuasive sanctioning system in Europe. The fact that penalties are left to the competence of the member states, which are culturally different and have different legal systems, has led to an alarmingly irregular implementation. From another perspective, with protection being put in second place, this leads to competitive distortion in the territory of the European Union. The article examines efforts made by European institutions and member states to improve the harmonisation of the application of Regulation (EC) No. 1/2005. It also offers practical inputs that can be used in future negotiations of the existing laws on animal transport.